CLIL and materials for learning: a rubric for analysis - Pimentel-Velázquez, Cynthia (European Public & Social Innovation Review, 2025)
Introduction: The development of tools for the analysis and evaluation of teaching materials used in bilingual contexts (CLIL) is still scarce. This paper reflects on the methodological principles that CLIL materials should comply with, with a triple objective: content and lan-guage learning and the development of literacy and presents a checklist for the analysis of materials. Methodology: the development of this checklist has considered the methodologi-cal principles for CLIL, especially the so-called "dimensions of literacy support". Results and discussion: The proposed checklist contains the dimensions based on the type of workplan (tasks, activities and academic questions), cognitive discourse functions (CDFs), text genres, communicative language activities (CLAs) and interaction. Conclusions: The scarce tools available to teachers in CLIL contexts to carry out the analysis of materials in these contexts make it necessary to carry out proposals that can be useful in a process that is often labori-ous, the checklist presented in this paper aims to be useful to teachers and contribute to a field, still under-studied.